Lokalitas dan Tekstualitas Tafsir Al-Iklil Fi Ma’ani Al-Tanzil Dalam Masyarakat Tradisional Jawa - Abd. Majid Abror (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2023)
The study of interpretation is a study that is very important to study, in general the study of interpretation uses Arabic which gives rise to the characteristics of Islam, but nowadays there are various interpretations, one of which is the Interpretation of the Archipelago. In the study of Interpretation of the Archipelago this is something that needs to be examined because in general not all people understand Arabic. In this discussion using library research methods (library research), namely research that examines and seeks information and data which as a whole comes from written language that is relevant to what is being studied. The results of the research are as follows: First, the book of tafsir al-Iklil Fi Ma'ani al-Tanzil has three localities namely 1). Locality in appearance using the Arabic script pegon and the meaning of gandul, 2). Locality in communication, 3). Locality in interpretation is criticizing local traditions and translations. Second, the textuality of the application of the interpretation of al-Iklil Fi Ma'ani al-Tanzil. Third, Tafsir al-Iklil Fi Ma'ani al-Tanzil as an object of study for traditional Javanese society.